ANTHROPOGENESIS DEFINATION, ZOOLOGICAL CONCEPTS - KIRAN KUMARI (International Journal of Multidisciplinary Research and Studies, 2020)
The Economist declared “Welcome to the Anthropocene” on its front page, and in 2013 a well-received series of art exhibitions in Berlin explored “The Anthropocene Project.” The moods around these discussions range from alarm and urgency, through wistful nostalgia or pragmatic management, to optimistic grasping of opportunity. The Anthropocene has become a scientific and cultural zeitgeist, a charismatic mega-category emerging from and encapsulating elements of the spirit of our age. It may be a passing cultural fad or end up as something more enduring; it is used in different ways by different users, but it is undoubtedly a core aspect of contemporary thinking about the environment.